INVESTIGATION OF THE USE OF STUDDED WINTER AND UNIVERSAL TIRES IN VEHICLES OF M1 AND N1 CATEGORIES IN ŠIAULIAI - Astrauskas, Darius (PROFESSIONAL STUDIES: Theory And Practice, 2023)
Tires are one of the most important elements of vehicles in terms of traffic safety. This is even more evident in unfavourable weather conditions on winter roads. The wrong choice of tires quite often becomes the cause of a traffic accident. It is very important to pay attention to the correct use of tires for drivers of trucks and cars. The vehicle is in contact with the road surface only on the four surfaces of the human palm. Road traffic safety depends on various traffic elements: driver education, road quality and technical condition of cars. Tires are one of the components of a car. This paper examines the types of tires suitable for use in winter, the tire tread patterns, in order to determine the types of winter tires used, the prevalence of studded tires is studied. The aim is to determine the reasons why some European countries prohibit the use of studded winter tires.